Height-Based Formula Predicting Renal Length in Korean Children derived from Technesium-99m Dimercaptosuccinic Acid Scan - Myung Hyun Cho; Ha Yeong Yoo; Byung Ok Kwak; Hye Won Park; Sochung Chung; Soo Nyung Kim; Jae Sung Son; Kyo sun Kim (Korean Society of Pediatric Nephrology, 2015)
Purpose: The aim of this study was to establish a simple formula to predict renal length in children using a Technesium-99m dimercaptosuccinic acid (DMSA) scan data, and to compare it with the formula derived from ultrasonography, which is widely accepted. Methods: Children who underwent a DMSA scan and ultrasonography were reviewed retrospectively, and those who had anatomical urinary tract abnormalities or urinary tract infections were excluded. Results: A total of 230 children (84 males and 146 females; age, 1 month to 16 years; mean age, 16.8 ± 27.4 months). Mean renal length measured by DMSA scan was longer than that by ultrasonography (6.38 ± 1.16 vs. 6.02 ± 1.14 cm; P < 0.001). Renal length was correlated with age, weight, height, and body surface area on the DMSA scan and ultrasonography, and showed the strongest positive correlation with height. The following formulae were established to predict renal length: mean renal length (cm) = 5.433 × height (m) + 2.330 (R2, 0.833) using the DMSA scan data, and mean renal length (cm) = 5.367 × height (m) + 2.027 (R2, 0.853) using ultrasonography data. Conclusion: We propose a simple height-based formula to predict renal length in children using a DMSA scan data, and validate it by comparing with ultrasonography formula.